Factors that determine the purchase intention of running shoes on digital platform - Lee, Yan Wei (2019)
Statistics had shown the athletic-footwear industry to be lucrative, with research identifying running shoes to be the main contributor to athletic-footwear monthly growth. With technological advancement, electronic commerce had been incorporated into the distribution channel of running shoes. This phenomenon coupled with the high participation rate of running/jogging in Singapore created a positive outlook in the running shoe industry. However, research in online running shoes retailing remains dearth and inconclusive.